Landslide risk analysis on agriculture area in Pacitan Regency in East Java Indonesia using geospatial techniques - Putra, Aditya Nugraha; Istika Nita; Al Jauhary, Muhammad Rifqi; Nurhutami, Shofie Rindi; Ismail, Mohd Hasmadi (Faculty of Environment and Resource Studies, Mahidol University, 2021)
Pacitan is one of the regencies in East Java Province, dominated by hills and mountain landforms covering 85% of its area. Since 2011, more than 16 landslides have occurred significantly in this area. These disasters have engulfed more than 350 ha of agricultural land in Pacitan. This study analyzed the risk of future landslides due to land use change. The parameters used were rainfall, slope, topography, geology, soil, and land use which were assessed and weighed by the Paimin method. Land-use classification from Landsat 8 OLI in 1998, 2008, and 2018 were analyzed using regression formula to calculate the trend of change in 2030. Land use was also classified from the land capability classification (LCC) and regional spatial planning (RSP) as land use options in 2030. The results showed that land use changed over time due to the changes in landslide hazards, which increased three-foldfrom 1998 to 2018 and will peak tremendously in 2030. There are 29.47 ha of agricultural land in 2018 that have a high potential landslide hazard if no intervention is made. The accuracy for prediction of the 2018 data mapping was 82%. The LCC strategy suggests land use planning to reduce a high level of the landslides.